Beauty and the beast - Wiesner; David (London Parent and Child, 2007)
The story follows Beauty, a kind young woman who finds herself living with a Beast after her father takes a rose from the Beast$1 (Bs enchanted garden. Despite the Beast$1 (Bs fearsome appearance, Beauty discovers his gentle heart and learns that he is under a spell. Through her kindness and bravery, Beauty helps break the curse, revealing the Beast$1 (Bs true form as a prince. The tale highlights themes of inner beauty, love, and the transformative power of compassion.s